Barriers to weight‐related health behaviours: a qualitative comparison of the socioecological conditions between pregnant and post‐partum low‐income women - Graham, Meredith (Matern Child Nutr, 2014)
The association between socioecological factors and poor health outcomes for low‐income women and their children has been the focus of disparities research for several decades. This research compares the socioecological conditions among low‐income women from pregnancy to post‐partum and highlights the factors that make weight management increasingly difficult after delivery. As part of the formative research for an online health intervention, group and individual interviews were conducted with low‐income pregnant and post‐partum women. Five pregnancy group interviews (n = 15 women), five post‐partum group interviews (n = 23 women) and seven individual interviews with a total of 45 participants were conducted in Rochester, New York. All interviews were audio‐recorded. The constant comparative method was used to code interview notes and identify emergent themes. Subjects faced many challenges that affected their attitudes, beliefs and their ability to maintain or improve healthy weight behaviours. These included unemployment, relationship issues, minimal social support, lack of education, limited health care access, pre‐existing medical conditions and neighbourhood disadvantage. Compared with pregnant women, post‐partum women faced additional difficulties, such as child illnesses and custody issues. The most striking differences between pregnancy and post‐partum related to the family's medical problems and greater environmental constraints. Many factors detracted from women's capacity to engage in healthy weight behaviours post‐partum, including challenges present prior to delivery, challenges present prior to delivery that worsen after delivery, and new challenges that begin after delivery. These additional post‐partum challenges need to be considered in designing programmes, policies and interventions that promote healthy weight.